Bio-based polyurethane foams toward applications beyond thermal insulation. (5th July 2015) - Gama, Nuno V.; Soares, Belinda; Freire, Carmen S.R.; Silva, Rui; Neto, Carlos P.; Barros-Timmons, Ana; Ferreira, Artur
Graphical abstract: Highlights: Coffee grounds wastes were successfully liquefied yielding a bio-based polyol. Coffee grounds derived foams formulations were optimized by tuning reagents' contents. The viscoelastic properties of these foams are promising to expand their applications. Abstract: In this work the preparation of viscoelastic bio-based polyurethane foams (PUFs) using polyols obtained via acid liquefaction of coffee grounds wastes has been optimized. In a first stage, the effect of different ratios of isocyanate content to hydroxyl number (0.6, 0.7 and 0.8) and of three distinct percentages of catalyst (3%, 5% and 7%) on the extent of the polymerization reaction was studied by infrared spectroscopy. Next, different percentages of surfactant (14%, 16% and 18%) and blowing agent (12%, 14% and 16%) were used to assess their effect on the density, thermal conductivity and mechanical properties of the foams, including their recovery time. The mechanical properties of the ensuing foams proved to be very interesting due to their viscoelastic behavior. PUFs were also characterized by scanning electron microscopy (SEM) revealing a typical cellular structure and by thermogravimetric analysis (TGA) which proved that these materials are thermally stable up to 190 °C. These results suggest other potential applications for these materials beyond heat insulation in areas where damping properties can be an added value.